循环肿瘤细胞有丝分裂指数在癌症分层和诊断中的应用 (2021)
在患者中，循环肿瘤细胞(CTC)与恶性实体肿瘤的转移有关。这里给出的证据是CTC表现出细胞周期阶段变异性，在有丝分裂细胞周期阶段CTC的数量与受试者长期存活的前景有很强的相关性，所述细胞来自所述受试者。本文还介绍了从癌症患者中确定CTC的有丝分裂细胞周期阶段的方法，并利用这些信息对恶性实体肿瘤进行分级，并预测患者存活的可能性。 Circulating tumor cells (CTCs) are associated with metastasis of malignant solid tumors in a patient. Presented here is evidence that CTCs exhibit cell cycle phase variability and that there is a strong correlation between the number of CTCs in a mitotic cell cycle phase and the prospects for long term survival of the subject from which the cells were obtained. Also presented herein are methods of determining the mitotic cell cycle phase of CTCs from a patient having cancer and using the information in grading malignant solid tumors and predicting the likelihood of survival of the patient.